2021
DOI: 10.3390/biomedicines10010016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Gut Microbiota in Individuals with Overweight or Obesity during a Real-World Weight Loss Dietary Program: A Focus on the Bacteroides 2 Enterotype

Abstract: Background: Dietary intervention is a cornerstone of weight loss therapies. In obesity, a dysbiotic gut microbiota (GM) is characterized by high levels of Bacteroides lineages and low diversity. We examined the GM composition changes, including the Bacteroides 2 enterotype (Bact2), in a real-world weight loss study in subjects following a high-protein hypocaloric diet with or without a live microorganisms (LMP) supplement. Method: 263 volunteers were part of this real-world weight loss program. The first phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
(102 reference statements)
0
16
0
Order By: Relevance
“…Interestingly, environmental fitting of biotin (vitamin B7/8 calculated from food consumption) on the PCoA ordination landscape pointed towards regions of the compositional space dominated by Prevotella enterotype, a microbial composition dominated by bacteria auxotrophic for biotin production 3 (Figure 3B), which is line with the significant positive association of biotin intake with the probability of Prevotella enterotype in the logistic regression analyses (Supplemental Figure 2, Supplemental Results). Several associations were reproduced in the second independent cohort of 433 individuals with overweight and obesity from the GutInside study 30 , where the QASD score was the variable with the highest and non-redundant explanatory power in microbiome compositional variation (Figure 3C). Environmental fitting showed that high QASD was also associated to Rum enterotype, whereas the aDII score was associated to Bact2 enterotype (Figure 3D).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Interestingly, environmental fitting of biotin (vitamin B7/8 calculated from food consumption) on the PCoA ordination landscape pointed towards regions of the compositional space dominated by Prevotella enterotype, a microbial composition dominated by bacteria auxotrophic for biotin production 3 (Figure 3B), which is line with the significant positive association of biotin intake with the probability of Prevotella enterotype in the logistic regression analyses (Supplemental Figure 2, Supplemental Results). Several associations were reproduced in the second independent cohort of 433 individuals with overweight and obesity from the GutInside study 30 , where the QASD score was the variable with the highest and non-redundant explanatory power in microbiome compositional variation (Figure 3C). Environmental fitting showed that high QASD was also associated to Rum enterotype, whereas the aDII score was associated to Bact2 enterotype (Figure 3D).…”
Section: Resultsmentioning
confidence: 91%
“…The intake of tyrosine, offal, “cereals, pasta and rice” and the variety of dairy products points to opposite direction in the compositional space (Figure 3B). The additional inclusion of the QASD score and the aDII score in the environmental fitting shows that high QASD score levels were also associated with the compositional space dominated by Rum enterotype, whereas the aDII and lower QASD score levels (0-2) were associated to compositional landscape dominated by Bacteroides 2 enterotype (Bact2), previously associated to both a lower GMGR and bacterial load, systemic inflammation and obesity severity 30,41 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…[9] Obesity is characterised by the dysbiosis of the gut microbiome. [10,11] The overall diversity of gut microbiota has been reported to decrease with increasing body mass index (BMI). [12,13] Moreover, studies on obese populations have also suggested the alterations in the ratio of Firmicutes and Bacteroidetes in the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%